2001
DOI: 10.1002/ajmg.1384
|View full text |Cite
|
Sign up to set email alerts
|

Low birth-weight, microcephalic malformation syndrome in a 46,XX girl and her 46,XY sister with agonadism: Third report of the Kennerknecht syndrome or autosomal recessive Seckel-like syndrome with previously undescribed genital anomalies

Abstract: We report on two sisters, one 46,XX with normal female phenotype, the other 46,XY with ambiguous external genitalia and agonadism. Both have a low birth weight and microcephalic malformation syndrome leading to early death. The 46,XX patient also had a diaphragmatic defect. The XY sister, in addition to absence of gonads and Mùllerian and Wolffian derivatives, had severe hypoplasia of the pulmonary artery and its branches, multicystic kidneys, and pachygyria. This combination of malformations, in part, fits in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Patient 1 (P1) and Patient 2 (P2) had frequent lower respiratory tract infections, with P1 dying of respiratory failure aged 10 years as a result of chronic lung disease. Furthermore, P1 had two siblings who died in early infancy 22 . However, aside from P2 who had a persistent lymphopenia, there was no evidence of adaptive immune deficits on clinical investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Patient 1 (P1) and Patient 2 (P2) had frequent lower respiratory tract infections, with P1 dying of respiratory failure aged 10 years as a result of chronic lung disease. Furthermore, P1 had two siblings who died in early infancy 22 . However, aside from P2 who had a persistent lymphopenia, there was no evidence of adaptive immune deficits on clinical investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Under this hypothesis, LB1 would have a short stature with microcephaly syndrome in which both body size and brain volume are far below the norms for the extant population. Various syndromes with severe intrauterine growth retardation and proportionate (at least at birth) microcephaly have been described in modern humans, including Bangstad, Bloom, Buebel, de Lange, Dubowitz, Kennerknecht, Meier-Gorlin, Okajima, and Seckel syndromes, as well as Majewski (microcephalic) osteodysplastic primordial dwarfism (MOPD) type 1, MOPD type 2, MOPD-Cervenka type, and MOPD-Toriello type (Toriello et al, 1986;Bangstad et al, 1989;Opitz and Holt, 1990;Meinecke et al, 1991;Lin et al, 1995;Buebel et al, 1996;Bongers et al, 2001;Silengo et al, 2001;Faivre et al, 2002;Okajima et al, 2002;Hall et al, 2004). Several of these syndromes are associated with survival to adulthood.…”
Section: Case For Microcephalymentioning
confidence: 99%
“…A literature review of reported cases suggests that agonadism, whether occurring with an XX or XY karyotype, could be variably associated with other extragenital malformations, including neural tube defects, omphalocele, congenital heart defects, diaphragmatic defects, and upper limb reduction [Kennerknecht et al, 1993[Kennerknecht et al, , 1995[Kennerknecht et al, , 1997Ohro et al, 1998;Silengo et al, 2001]. In addition, the fetus we described and the case reported by Kennerknecht et al [1997] probably represent the severe end of the clinical spectrum.…”
Section: Discussionmentioning
confidence: 67%